Assessment of the effect of technical and management characteristics on the frequency of release from piping: An application to a gas storage facility. (July 2021) - Milazzo, Maria Francesca; Uguccioni, Giovanni; Malatesta, Giuliano; Miglionico, Roberta; Tallone, Fabrizio
Abstract: The assessment of the frequencies of release from piping due to losses of containment is an essential step in the preparing Safety Reports, drawn up as required by the so-called "Seveso" Directive. These are usually calculated starting from the frequencies of random rupture included in international databases and are not plant-specific, furthermore, the quantification of the effect of the safety management system of the facility is not easy. A simple and flexible approach quantifying technical and management characteristics of the plant has been proposed by Milazzo and co-workers in 2010; it is based on the modification of the frequency taken from literature, through the use of the percentages of failure causes actually possible in that plant, and the judgment about their management. The data about the failure causes are taken from the literature and modified by using corrective factors to adapt them to the industrial context. To make possible the application of the method to a large number of major-hazard industry types, some aspects of the approach needed to be improved; these have been identified during a development project coordinated by RINA Consulting, on behalf of Saipem, with the collaboration of the University of Messina. The improvement of the approach focused on two main points, the development of a method to calculate the corrective factors for the failure causes associated with corrosion and erosion phenomena and the strengthening of the methodology for the formulation of the judgment about the safety management. This paper illustrates the fully improved method, as well as an application to a typical gas storage plant. Highlights: The effect of the safety management on the rupture frequency of piping is quantified. The percentages of failure cause are the weights modifying the frequency. The weights are modified to make them plant-specific. The judgement indicates the capability to prevent or not the failure causes. The study made the method applicable to various major-hazard contexts.